EFEKTIVITAS PENAMBAHAN EKSTRAK MESOCARP Borassus flabellifer PADA PENGENCER BELTSVILLE THAWING SOLUTION TERHADAP VIABILITAS SPERMATOZOA ASAL KAUDA EPIDIDIMIS BABI - Hermilinda Parera; Bernadus Ndoen; Victor Lenda; Muhammad Mirandy Pratama Sirat (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
This study aimed to determine the effectiveness of adding various concentrations of palm fruit mesocarp (Borassus flabellifer) extract to Beltsville Thawing Solution (BTS) diluents on the viability of swines cauda epididymis spermatozoa at 13°C for 4 days. During the storage period, the metabolic activity of spermatozoa will produce free radicals which can reduce spematozoa viability. Borassus flabellifer mesocarp extract contains antioxidants that can counteract free radicals. Testicular and epididymal samples from the 3-4 years old Duroc Landrace Swine Crossbreed. Swine cauda epididymis were obtained from the Oeba Abattoir, Kupang. Cauda epididymis spermatozoa were collected using a combination of incision, rinsing and suppression methods then collected and diluted using BTS and divided into four groups to be given various concentrations of Borassus flabellifer mesocarp extract (K0: without extract; K1: 0.01%; K2: 0.03%; and K3: 0.05 %) and preserved at 13°C for 4 days. Evaluation of spermatozoa viability was carried out microscopically. The results of cauda epididymis sperm viability were K0 = 43.57%; K1 = 54.81%; K2 = 50.52%; and K3 = 49.95%. Analysis of variance showed that the addition Borassus flabellifer mesocarp extract gave a significant difference (P> 0.05) to spermatozoa viability. The Duncan region test showed a significant difference (P <0.05) between treatment K1 with treatments K0, K2 and K3 on the viability of spermatozoa. The conclusions of this study was the addition of Borassus flabellifer mesocarp extract at 0.01% concentration was the most appropriate dose to maintain the viability of swine cauda epididymis spermatozoa. Keywords: Borassus flabellifer, Cauda Epididymal, Mesocarp Extract, Spermatozoa, Swine.